ALIGNING AI WITH ISLAMIC VALUES: A COMPREHENSIVE SYSTEMATIC LITERATURE REVIEW ON ETHICAL HORIZONS - FUADY ABDULLAH; YUDI ACHMAD BASHORI (Hamdard Islamicus, 2026)
This study examines the systematic integration of Islamic ethical principles into the development and application of artificial intelligence (AI). The primary research inquiries focus on the frameworks proposed to bridge the divide between normative theory and practical design, also the extent to which contemporary scholarship examines the congruence of AI with Islamic ethics. The review underscores several critical issues, including the restricted scope of contemporary research and the discord between universal ethical principles and their implementation in Muslim society. A stringent keyword strategy was employed to extract data from the Scopus database, resulting in 104 relevant publications from 2016 to 2025. A mixed-methods approach was employed: qualitative content analysis of ethical discussions and theoretical frameworks, whereas bibliometric techniques, such as citation analysis, bibliographic coupling, and keyword co-occurrence mapping, quantitatively elucidated research trends, significant sources, and collaborative networks. The findings identify three main directions: the design of AI frameworks based on Islamic ethics, investigation of challenges and opportunities of AI use, and understanding wider implications for human values inclusive for AI. The study illustrates that incorporating Islamic values in AI design is important to build technologies reflecting cultural context of use, social acceptability and moral justifiability, thereby helping to promote responsible and ethical AI development.